Intrapersoonlike transformasie by pastors – die paradoks van emosionele verwonding as bron tot genesing - Nolte, S. Philip (HTS teologiese studies, 2009)
Interpersonal transformation of pastors – the paradox of emotional trauma as source to healingThis article reflects upon the way in which the interplay between reason and emotion influences pastors’ lives and ministry. It studies the process of inner transformation as a meaningful way for pastors to become ‘healed healers’. Inner transformation is described in terms of Aristotle’s phronēsis and Paul Ricoeur’s movement from mimēsis1 to mimēsis3. The article agrues that ‘healing’ in no way purports that pastors are able to heal others in a literal sense, but merely that by being conscious of their own wounds, pastors can experience the paradox that their own wounds could become a source of healing. This approach to woundedness is interpreted from two distinct perspectives. Firstly, it is seen from the perspective of Jesus as the human face of God. Jesus’ emotional disposition towards the nobodies of his time is seen as paradigmatic for pastors’ relationships with others. Secondly, woundedness is seen within the context of the metaphor of the wounded healer as narrated in ancient Greek mythology, and used by Carl Jung in a psychiatric setting. It is not only pastors’ knowledge of the Bible, theological tradition and different pastoral and other therapeutic theories, models and methods that facilitates meaningful interaction between themselves and others. Central to pastors’ role as wounded healers is their conscious acknowledgement of their own humanity and therefore their own woundedness.